2013
DOI: 10.3109/00207454.2013.856902
|View full text |Cite
|
Sign up to set email alerts
|

Vascular factors are associated with the severity of the neuropsychiatric symptoms in Alzheimer's disease

Abstract: Presence of hypertension and asymptomatic stroke are related with the severity of apathy and depression in Alzheimer's dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Behavioral differences between patients with and without HTN were also observed in specific items of NPI such as delusions, depression, anxiety, apathy, disinhibition, irritability, and nighttime behaviors. This finding is consistent with the results of some studies that have found that a history of HTN increases the risk of BPSD such as depression/dysphoria, anxiety, and apathy in AD patients 34,35 . In a study of older AD patients, VRFs were associated with a greater risk of delusion, depression, and agitation 36 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Behavioral differences between patients with and without HTN were also observed in specific items of NPI such as delusions, depression, anxiety, apathy, disinhibition, irritability, and nighttime behaviors. This finding is consistent with the results of some studies that have found that a history of HTN increases the risk of BPSD such as depression/dysphoria, anxiety, and apathy in AD patients 34,35 . In a study of older AD patients, VRFs were associated with a greater risk of delusion, depression, and agitation 36 .…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with the results of some studies that have found that a history of HTN increases the risk of BPSD such as depression/dysphoria, anxiety, and apathy in AD patients. 34,35 In a study of older AD patients, VRFs were associated with a greater risk of delusion, depression, and agitation. 36 suggesting that the degeneration of the medial temporal lobe may be closely correlated with the emergence of some BPSD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, results should be interpreted with caution. Two of the studies that investigated the relationship between apathy and white matter morphometry by means of visual rating of structural (T1-and T2 weighted) MRI-scans did not find specific associations (Holthoff et al, 2005;Moon et al, 2014a). Lastly, one study investigating volumetric characteristics of the brain's white and gray matter, did not find an association with apathy (Starkstein et al, 2009).…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 96%
“…Many data established a possible link between apathy and AD with a decreased reliability of ACC network, mainly due to an increased generalized amyloid depositions (Canevelli et al, 2013), a volume loss in ACC (Apostolova et al, 2007; Bruen et al, 2008; Marshall et al, 2013; Stanton et al, 2013), a decreased perfusion in ACC (Benoit et al, 2004; Lanctôt et al, 2007; Tunnard et al, 2011), a decreased ACC white matter related integrity (Robert et al, 2006; Kim et al, 2011; Hahn et al, 2013), and increased amyloid burden in right ACC (Ota et al, 2012; Mori et al, 2014). Apathy is also associated with decreased posterior cingulate (PCC metabolism; Migneco et al, 2001), with a reduced insular volume (Moon et al, 2014a; Delrieu et al, 2015), and with decreased inferior temporal cortical (ITC) thickness (Moon et al, 2014b; Guercio et al, 2015), with cortical shrinkage of the frontal cortex (Apostolova et al, 2007; Bruen et al, 2008; Marshall et al, 2013; Stanton et al, 2013), with greater amyloid burden in bilateral frontal cortex (Ota et al, 2012), reduced orbitofrontal metabolism on the left (Donovan et al, 2014) or right (Benoit et al, 2004), and reduced connectivity in left-sided functional connectivity, with thalamus and parietal cortex, and amygdala (Holthoff et al, 2005; Kang et al, 2012; Ota et al, 2012; Baggio et al, 2015). Galantamine, as a cholinesterase inhibitor has been linked to a slower decrease of the putamen metabolism (Zhao et al, 2014), based on FDG-PET study (Zhao et al, 2014).…”
Section: What Do We Know About Apathy From Clinical Practice?mentioning
confidence: 99%